Comparison Of Isoconazole Nitrate Versus Nystatin For The Treatment Of Otomycosis - Amna Kausar; Sadia Chaudhry; Nighat Qammar; Ansa Umara Akram; Ashar Alamgir; Wajid Hussain (Journal of Rawalpindi Medical College)
Objective: To compare the efficacy and local adverse effects of Isoconazole Nitrate versus Nystatin for the treatment of patients having Otomycosis